Perlindungan Korban Kekerasan dalam Rumah Tangga di Kabupaten Timor Tengah Selatan - Debora Apriani Nabuasa; Debi F. Ng. Fallo; Rosalind Angel Fanggi (Bhirawa Law Journal, 2026)
This study aims to analyze the legal protection of victims of domestic violence and to identify the obstacles faced in its implementation in Timor Tengah Selatan Regency. This research employs an empirical juridical method with a qualitative descriptive approach, combining primary data obtained through interviews with Head of PPA Unit and Head of UPT DP3A , as well as secondary data derived from legal regulations and literature. The results indicate that, normatively, the protection of domestic violence victims has been regulated under Law Number 23 of 2004; however, its implementation in practice remains suboptimal. The forms of protection include legal, physical, and psychological support provided by the police and the Office of Women’s Empowerment and Child Protection (DP3A). Nevertheless, several internal and external challenges persist, such as limited human resources, lack of inter-agency coordination, inadequate supporting facilities, and low public legal awareness. Additionally, patriarchal cultural factors, social stigma, and victims’ economic dependence on perpetrators contribute to the low reporting rate of domestic violence cases. Therefore, it is necessary to strengthen institutional synergy, enhance the capacity of law enforcement officers, and increase public awareness to improve the effectiveness of victim protection.